2020
DOI: 10.1002/jbmr.4723
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Bone Quality in a Transgenic Mouse Model of Alzheimer′s Disease

Abstract: Alzheimer′s disease (AD) patients present with symptoms such as impairment of insulin signaling, chronic inflammation, and oxidative stress. Furthermore, there are comorbidities associated with AD progression. For example, osteoporosis is common with AD wherein patients exhibit reduced mineralization and a risk for fragility fractures. However, there is a lack of understanding on the effects of AD on bone beyond loss of bone density. To this end, we investigated the effects of AD on bone quality using the 5XFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…Aβ42 can potently enhance osteoclast differentiation and activation but does not affect osteoclast cell viability or number ( 27 ). One study observed that 5XFAD mice had decreased volumetric BMD, elevated endocortical bone loss and reduced mineralization with smaller mineral crystals ( 28 ). Two pathways were found to be contributing to skeletal fragility in AD via alteration of bone quality: accumulation of AGEs and lack of crystallinity, reduced crystal size, and lack of mineralization ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aβ42 can potently enhance osteoclast differentiation and activation but does not affect osteoclast cell viability or number ( 27 ). One study observed that 5XFAD mice had decreased volumetric BMD, elevated endocortical bone loss and reduced mineralization with smaller mineral crystals ( 28 ). Two pathways were found to be contributing to skeletal fragility in AD via alteration of bone quality: accumulation of AGEs and lack of crystallinity, reduced crystal size, and lack of mineralization ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study observed that 5XFAD mice had decreased volumetric BMD, elevated endocortical bone loss and reduced mineralization with smaller mineral crystals ( 28 ). Two pathways were found to be contributing to skeletal fragility in AD via alteration of bone quality: accumulation of AGEs and lack of crystallinity, reduced crystal size, and lack of mineralization ( 28 ). Another animal study showed that endogenous Aβ might induce osteoporosis via mTOR-dependent inhibition of autophagy in bone marrow mesenchymal stem cells (BMSCs) ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…While we were writing our manuscript, another report described the skeletal phenotype of 5xFAD mice, revealing decreased mineralization, toughness, and quality of cortical bone with endocortical bone loss in both male and female 5xFAD mice at the age of 12 months ( LLabre et al, 2022 ). While sympathetic nervous system activity or circadian clock gene expression was not evaluated, the bone phenotype was found to reflect the accumulation of advanced glycation end products in the bone matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Sex is one of the major risk factors for AD, with a higher incidence of the disease in females [ 41 ]. Osteoporosis is a common complication in women with AD, with patients exhibiting reduced mineralization and risk of fragility fractures [ 42 ]. Estrogen deficiency, in light of menopause, has distinctly been recognized as a major risk factor for osteoporosis in women [ 42 ].…”
Section: Discussionmentioning
confidence: 99%